ANTHROPOMETRIC PROFILE OF GROUP OF CHILDREN AND YOUTH WITH HEARING DISABILITIES ASSISTED IN AN INSTITUTION OF REFERENCE MACAÉ, RIO DE JANEIRO (Fiep Bulletin - online, 2013)
In young people, nutritional problems, especially in developing countries, such as malnutrition and obesity, stems, among others, changes in eating habits. This picture has been reflecting on the increased prevalence of chronic non-communicable diseases, particularly in adulthood. Currently, there are few published studies that identify nutritional risks in the population of children and adolescents with hearing impairment.The present study aimed to evaluate the anthropometric profile of children and adolescents with hearing deficiency in a reference institution in Macaé, Rio de Janeiro. This is a cross-sectional study fulfilled with 23 children and hearing impaired adolescents, between 07 and 19 years 11 months 29 days of age, observed at the Macaense Association of Deaf (AMADA) during the period August 2011 to August 2012, that accepted and consented in writing through their legal guardian, after reading the Informed Consent and containing clarified explanations about the objectives of the study and procedures to be performed. Interviewers collected anthropometric measurements of weight and height, beyond age and gender. The anthropometric indicators used were H/A; BMI by age. The study evaluated 23 individuals, 73.9% adolescents and 26.1% children. In the anthropometric evaluation, the average values (± SD) BMI by age of children and adolescents were 18.85±5.36 and 18.76±3.4kg.m2 respectively. The study revealed that 83.3% of the students were with height within the normal range and 16.7% with short stature. Among the adolescents, 94.1% were within normal height and 5.9% had short stature for his age. It was concluded that 1/3 of children were obese. It is necessary to draw up intervention measures and develop new studies.
Keywords: Deaf; Hearing Loss; Hearing impaired persons.